The Effect of STEAM Project-Based Learning Approach Towards Student Learning Motivation: Utilization of Plastic Waste with Ecobricks Technique - Leasa, Marleny; Ginting, Cristina; Tarigan, Haganta; Kolatlena, Lusiana; Batlolona, John Rafafy; Edike, Uche Emmanuel (FKIP Universitas Lampung, 2024)
The exponential increase in plastic production and the surge in plastic waste have led scientists and researchers to look for innovative and sustainable ways to recycle plastic waste to reduce its negative environmental impact. Project-Based Learning (PjBL) based on STEAM (Science, Technology, Engineering, and Mathematics) with ecobricks is one of the learning solutions for reducing plastic waste and increasing student motivation. This study aimed to determine the effect of the STEAM-based PjBL model with ecobricks techniques that can improve student learning motivation on ecology. This type of research is pre-experimental One-Group Pretest-Posttest Design. The sample in this study was 25 respondents. The sampling technique used by researchers was purposive sampling. The results of the study showed that based on the pretest in this study 55.28 after treatment was given to 25 respondents, the posttest results were 74.96. Other findings also showed a difference in the average value between the pretest and posttest. The sig. (2-tailed) value of 0.001 <0.05 then H0 is rejected and Ha is accepted, meaning that the steam-based project-based learning model is effective in increasing student learning motivation. Thus, STEAM-based PjBL with ecobricks techniques can improve the learning motivation of elementary school students. Keywords: PjBL, STEAM, ecobricks, learning motivation.DOI: http://dx.doi.org/10.23960/jpmipa/v25i2.pp512-529